Spinning flange ring and forming technology thereof - Liu Chenggui; Pan Zhaoxing; Jin Chongli (2016)
The invention belongs to the technical field of automobile accessories, and particularly relates to a spinning flange ring and a forming technology thereof. The spinning flange ring comprises a flange ring body and a central inner hole. The inner wall of the flange ring body is of a groove structure. The ring body with the outer wall smoothly protruding surrounds the central inner hole. The spinning flange ring is manufactured through the first step of feeding, the second step of punching, the third step of inclination pressing, the fourth step of spinning forming, the fifth step of punching, the sixth step of inner circle turning, and the seventh step of outer circle turning and small hole drilling. The flange ring is manufactured through the spinning technology, the shape of a blank is preprocessed, part of the outer edge of the blank is pressed down, positioning is achieved through the central hole, and no cracks or wrinkles can appear in the spinning process; meanwhile, by means of the spinning technology